MODEL MANAJEMEN SEKOLAH MENENGAH ATAS ABAD XXI - Lantip Diat Prasojo (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: A Model of the Senior High School Management in the 21st Century.Globalization brings about wide impacts, including demands for development inthe educational field. The development of secondary education, especially seniorhigh schools, needs to be well planned in order that it can be well implemented.One of the problems arising in the senior high school development is one related tomanagement. This can be solved using a reliable management model, called amodel of the senior high school management in the 21st century. This model isbased on five principles, i.e.: (1) improvement of the quality of senior high schools,(2) implementation of modern management, (3) implementation of balancedscorecard, (4) implementation of good governance, and (5) application anddevelopment of ICT.Keywords: management model, 21st century management system